Anticipatory grief therapy for older persons nearing the end of life. (February 2013) - Cheng, Joanna OY; Lo, Raymond SK; Woo, Jean
Aging brings about multiple and accumulating losses over a long trajectory of illness with deterioration in overall functioning with secondary losses in social and existential domains. The reality of anticipatory grief (AG) in older patients facing the end of life is easily overlooked with little provision of psychosocial support, especially for those aging in institutions without integrated palliative care services. This article discusses the challenges that AG poses for the older patients, as well as the desired therapeutic outcomes through using this approach. The evidence base for AG therapy has been limited. Beneficial therapeutic approaches for AG-related constructs will be reviewed, with recommendations to design interventions that target the AG of older patients facing different advanced conditions. AG interventions successfully implemented in the end-of-life care pathway may ensure optimal palliative care for the family.